Predicting nutritional status during pregnancy by women's empowerment in West Shewa Zone, Ethiopia - Etea, Tizita Dengia; Yalew, Alemayehu Worku; Sisay, Mitike Molla; Shiferaw, Solomon (Frontiers in Global Women's Health, 2023)
Background Considerable proportions of pregnant women are affected by poor nutrition outcomes in Ethiopia. Women's empowerment, on the other hand, is highly recognized as a means to achieve better maternal nutrition outcomes. However, the role of pregnant women's empowerment in nutritional status during pregnancy has not been empirically examined in Ethiopia. This study aimed to address this gap. Objective To assess the association of individual and composite women's empowerment dimensions with pregnant women's nutrition outcomes in West Shewa Zone, Ethiopia. Methods A health facility-based cross-sectional study was performed on 1,453 pregnant women living in West Shewa Zone, Ethiopia, in 2021. Exploratory and confirmatory factor analyses were conducted on half of the samples to identify and validate dimensions of pregnant women's empowerment. The associations between pregnant women's empowerment dimensions and anemia status and mid upper arm circumference levels were examined by logistic regressions. Results Composite pregnant women's empowerment was positively associated with both anemia status and mid-upper-arm circumference level. The odds of not being anemic were higher among pregnant women empowered in economic [adjusted odds ratio (AOR) = 1.7, 95% confidence interval (CI): 1.26, 2.22] and assertiveness (AOR = 1.9, 95% CI: 1.46, 2.38) dimensions than those not empowered in these dimensions. Empowered pregnant women in household decision-making (AOR = 1.6, 95% CI: 1.19, 2.22) and psychological (AOR = 1.4, 95% CI: 1.04, 1.85) dimensions had higher odds of having normal mid-upper-arm circumference measures than those not empowered in the respective dimensions. Communication and time dimensions were not significantly associated with any of the nutrition outcomes. Conclusions This study suggests that empowered pregnant women are nutritionally better off than their less empowered counterparts. This is also important in child health outcomes. Policies and programs that aim to improve maternal and child health in the study area need to consider interventions that promote the decision-making power, economic, psychological, and assertiveness dimensions of pregnant women.